Mesoscopic neural representations in spatial navigation - Kunz, Lukas (Trends Cogn Sci, 2019)
Recent evidence suggests that mesoscopic neural oscillations measured via intracranial electroencephalography exhibit spatial representations, which were previously only observed at the micro- and macroscopic level of brain organization. Specifically, theta (and gamma) oscillations correlate with movement, speed, distance, specific locations, and goal proximity to boundaries. In entorhinal cortex, they exhibit hexadirectional modulation, which is putatively linked to grid cell activity. Understanding this mesoscopic neural code is crucial because information represented by oscillatory power and phase may complement the information content at other levels of brain organization. Mesoscopic neural oscillations help bridge the gap between single-neuron and macroscopic brain signals of spatial navigation and may provide a mechanistic basis for novel biomarkers and therapeutic targets to treat diseases causing spatial disorientation.